2019
DOI: 10.1002/aoc.5062
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium catalyzed amide formation without water scavenging

Abstract: A scalable homogeneous metal‐catalyzed protocol for direct amidation of carboxylic acids is presented. The use of 2–10 mol% of the commercially available Zr(Cp)2(OTf)2·THF results in high yields of amides at moderate temperature, using an operationally convenient reaction protocol that circumvents the use of water scavenging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…In a very recent report, the same group disclosed a water-tolerant zirconium system that does not require a dehydrating agent. [82] It was found that zirconium (IV) bis(cyclopentadieneyl)bistriflate was uniquely active compared to the corresponding hafnium or bischloride variant of this species.…”
Section: Borate and Borinic Acid Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent report, the same group disclosed a water-tolerant zirconium system that does not require a dehydrating agent. [82] It was found that zirconium (IV) bis(cyclopentadieneyl)bistriflate was uniquely active compared to the corresponding hafnium or bischloride variant of this species.…”
Section: Borate and Borinic Acid Catalystsmentioning
confidence: 99%
“…Truong [96] ZrCl 4 THF 70 10 4 Å M.S. Adolfsson [81] ZrCp 2 (OTf) 2 THF 70 2 None Adolfsson [82] F I G U R E 1 0 Chelation promoted Tantalum catalyzed amidation of β-amino acids fromin-situgenerated silyl esters. R 1 = OAlkyl, Aryl.…”
Section: Other Metalsmentioning
confidence: 99%
“…In these reactions, carboxylic acids usually require additional steps and/or reagents to facilitate NH 2 attack, substantially decreasing process efficiency by increasing waste generation and energy consumption. Catalysis has been explored as an alternative to streamline amide synthesis, resulting in amide bond formations directly from nonactivated carboxylic acids and amines catalyzed mainly by boron and group IV/V metal catalysts . Notably, catalytic peptide bond formation remains underdeveloped, despite advancements featuring boron-, metal-, , and organocatalysts reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…2,[16][17][18][19][20][21][22] In addition, the use of protic acids has been explored to a lesser extent [23][24][25][26][27] Tetravalent metal complexes with fluoroalkylsulfonate ligands constitute an interesting class of water-stable Lewis acidic catalysts for a variety of transformations. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Despite this, this catalyst class is hardly represented in the context of dehydrative substitution of alcohols in contrast to its trivalent (and bivalent) counterparts. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] In direct etherification, two alcohols are joined with loss of water.…”
Section: Introductionmentioning
confidence: 99%